The Influence of Motivation and Job Satisfaction on Employee Performance at PT. Sustraco Adikreasi - Arista, Juliana; Darto, Darto (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
This study examines the effect of motivation and job satisfaction on employee performance at PT Sustraco Adikreasi. This topic is important because employee performance directly impacts the organisation's success. Despite numerous studies on similar variables, limited research investigates this relationship in the corporate context of PT Sustraco Adikreasi, highlighting its novelty. This study contributes to the literature by providing empirical evidence and practical insights into the role of motivation and satisfaction in improving performance. An associative quantitative method was used by distributing questionnaires to 50 respondents. Data were analysed using multiple linear regression, t-test, F-test, and coefficient of determination with the help of SPSS software. The findings show that motivation and job satisfaction positively and significantly influence employee performance individually and simultaneously. The results show that increasing motivation and satisfaction can significantly improve work performance. Keywords: Motivation, job satisfaction, employee performance